Non-structural carbohydrate dynamics and growth in tomato plants grown at fluctuating light and temperature - Zepeda, Ana Cristina; Heuvelink, Ep; Marcelis, Leo F. M. (Frontiers in Plant Science, 2022)
Fluctuations in light intensity and temperature lead to periods of asynchrony between carbon (C) supply by photosynthesis and C demand by the plant organs. Storage and remobilization of non-structural carbohydrates (NSC) are important processes that allow plants to buffer these fluctuations. We aimed to test the hypothesis that C storage and remobilization can buffer the effects of temperature and light fluctuations on growth of tomato plants. Tomato plants were grown at temperature amplitudes of 3 °C or 10 °C (deviation around the mean of 22°C) combined with integration periods of 2 or 10 days. Temperature and light were applied in Phase (high temperature simultaneously with high light intensity, (400 µmol m-2 s-1), low temperature simultaneously with low light intensity (200 µmol m-2 s-1) or in Antiphase (high temperature with low light intensity, low temperature with high light intensity). A control treatment with constant temperature (22 °C) and a constant light intensity (300 µmol m-2 s-1) was also applied. After 20 days all treatments had received the same temperature and light integral. Differences in final structural dry weight were relatively small, while NSC concentrations were highly dynamic and followed changes of light and temperature (a positive correlation with decreasing temperature and increasing light intensity). High temperature and low light intensity lead to depletion of the NSC pool, but NSC level never dropped below 8% of the plant weight and this fraction was not mobilizable. Our results suggest that growing plants under fluctuating conditions do not necessarily have detrimental effects on plant growth and may improve biomass production in plants. These findings highlight the importance in the NSC pool dynamics to buffer fluctuations of light and temperature on plant structural growth.